2016
DOI: 10.1007/s10295-016-1794-y
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and metabolic responses of Staphylococcus aureus in mixed culture with Lactobacillus plantarum, Streptococcus thermophilus and Enterococcus durans in milk

Abstract: Staphylococcus aureus is a major food-borne pathogen due to the production of enterotoxin and is particularly prevalent in contaminated milk and dairy products. The lactic acid bacteria (LAB) are widely used as biocontrol agents in fermented foods which can inhibit pathogenic flora. In our work, we investigated the influence of three strains of LAB (Lactobacillus plantarum, Streptococcus thermophilus and Enterococcus durans) on the relative expression of three enterotoxin genes (sea, sec, sell) and eight virul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…These results indicate that the production of SE by S. aureus was suppressed when C. scindens was present, but this suppression was not reliant on the creation of secondary bile acids. Similar findings have been observed in co-cultures of S. aureus with other bacterial species in vitro (Zdenkova et al, 2016;Nogueira Viçosa et al, 2019;Rodríguez-Sánchez et al, 2022). However, it is noteworthy that this phenomenon was observed for the first time in S. aureus-C. scindens co-culture in the presence of colonic cells.…”
Section: Measurement Of Staphylococcus Aureussupporting
confidence: 86%
“…These results indicate that the production of SE by S. aureus was suppressed when C. scindens was present, but this suppression was not reliant on the creation of secondary bile acids. Similar findings have been observed in co-cultures of S. aureus with other bacterial species in vitro (Zdenkova et al, 2016;Nogueira Viçosa et al, 2019;Rodríguez-Sánchez et al, 2022). However, it is noteworthy that this phenomenon was observed for the first time in S. aureus-C. scindens co-culture in the presence of colonic cells.…”
Section: Measurement Of Staphylococcus Aureussupporting
confidence: 86%
“…The pathogenic effects of S. aureus are connected with enterotoxin production in food matrix. It has been proved that 5 × 10 5 cells of enterotoxin-producing S. aureus strains per ml is a threshold value resulting in the production of enterotoxin [39,40]. Therefore, the key prevention should be to eliminate any factors and conditions that enhance the growth of the pathogen and the production of enterotoxin [41].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, S. aureus count decreased below the detection limit after 72 h of incubation when milk was inoculated with 3 log CFU/ml of both L. plantarum and S. aureus [42]. It was also shown that presence of S. aureus in co-culture with some L. plantarum strains slows down the pH lowering in the matrix, which could be the reason of overdue the effect of exhibited anti-staphylococcal efficiency [40].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of several enterotoxins and global regulator genes (including agr) was downregulated, while the expression of genes involved in metabolism was upregulated. Finally, the interaction of S. aureus with a mixed culture of Enterococcus durans, E. faecalis and L. lactis in milk confirmed that the production of enterotoxins was reduced in mixed culture and the expression of several genes involved in virulence was inhibited (Zdenkova et al, 2016). All these studies on the interaction of S. aureus with different lactic acid bacteria converge on a very important idea that the mechanism of action of biopreservation can result in the inhibition of virulence by inhibiting the production of enterotoxins through the decreased expression of genes involved in their synthesis.…”
Section: Staphylococcus Aureusmentioning
confidence: 81%